Asian dust transport of proteinaceous matter from the Gobi Desert to northern China - R.-G. Zhu; R.-G. Zhu; H.-Y. Xiao; M. Yin; H. Xiao; Z. Zhou; Y. Pan; G. Wei; C. Liu (Atmospheric Chemistry and Physics)
Asian dust can greatly influence the ecosystem's productivity and biogeochemical cycles by providing new nutrients. However, the transport of proteinaceous matter (combined amino acids, CAAs) by Asian dust to downwind ecosystems remains unclear. Here, the concentrations and δ15N values of individual CAAs in Gobi surface soil and vegetation and in PM2.5 samples from four cities in northern China were characterized. Proline dominated the total pool of CAAs in urban PM2.5 during non-dust periods, whereas CAAs transported by Gobi dust were rich in alanine, glycine and glutamic acid. The concentrations and percentages of these three CAAs in PM2.5 from northern China notably increased during dust periods. During non-dust periods, the δ15N values of individual CAAs in urban PM2.5 fell within their respective ranges in local urban sources, suggesting CAAs in PM2.5 were primarily influenced by local urban sources during non-dust periods. Compared to their values in urban PM2.5 during non-dust periods, glycine and leucine in Gobi Desert sources exhibited δ15N depletion by more than 6 ‰. During dust periods, glycine and leucine in urban PM2.5 all exhibited negative shifts in their δ15N values, confirming that Gobi dust is a significant source of CAAs in PM2.5 in northern China. The dry deposition of protein N from Gobi dust was calculated using nitrogen isotopic mass balance based on the δ15N values of glycine and leucine, yielding a value of up to 0.36 mg<mspace width="0.125em" linebreak="nobreak"/>N<mspace width="0.125em" linebreak="nobreak"/>m-2<mspace width="0.125em" linebreak="nobreak"/>d-1<svg:svg xmlns:svg="http://www.w3.org/2000/svg" width="65pt" height="15pt" class="svg-formula" dspmath="mathimg" md5hash="787367e437607d26f339866a2c6a9eb0"><svg:image xmlns:xlink="http://www.w3.org/1999/xlink" xlink:href="acp-25-7699-2025-ie00001.svg" width="65pt" height="15pt" src="acp-25-7699-2025-ie00001.png"/></svg:svg>. The rapid accumulation of such considerable protein N quantities may profoundly affect oligotrophic ecosystem productivity.